2021
DOI: 10.1055/s-0041-1731339
|View full text |Cite
|
Sign up to set email alerts
|

Patient Portals: Useful for Whom and for What? A Cross-Sectional Analysis of National Survey Data

Abstract: Background Patients who use patient portals may be more engaged and empowered in their care; however, differences in who accesses patient portals remain. The characteristics of who uses patient portals more frequently and who perceives them as useful may also differ, as well as which functions people use. Objective We assessed the characteristics of patient portal users to examine who uses them more frequently and who perceives them as useful. In addition, we wanted to see if those who use them more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Consistent with previous studies, 9,[17][18][19]21,22,[26][27][28]37,38 we found that portal users were more likely to be younger, female, non-Hispanic White, be privately insured, have higher CCI scores and more likely to live in areas with a higher median income and higher educational attainment. A study of the 2017 and 2018 Health Information National Trends Survey (HINTS) showed higher odds of portal use in respondents with a bachelor's degree and incomes in the middle tertile.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous studies, 9,[17][18][19]21,22,[26][27][28]37,38 we found that portal users were more likely to be younger, female, non-Hispanic White, be privately insured, have higher CCI scores and more likely to live in areas with a higher median income and higher educational attainment. A study of the 2017 and 2018 Health Information National Trends Survey (HINTS) showed higher odds of portal use in respondents with a bachelor's degree and incomes in the middle tertile.…”
Section: Discussionsupporting
confidence: 91%
“…Adjusted odds ratios (aOR) included adjustments for the random effect and fixed effects. We included predictors based on previous studies 9, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and from significant bivariable statistical tests. To simplify the evaluation of results we categorized ACS estimates into quartiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although more than 90% of providers offer patient portals, only one-third of patients enroll in them [ 6 •]. And the likelihood of enrollment is lower for patients among racial and ethnic minority groups, who are over 65 years old, and who have low income, low health literacy, or chronic illness [ 7 , 8 , 9 •, 10 •, 11 ]. A factor that might contribute to low enrollment is opt-in policies.…”
Section: Introductionmentioning
confidence: 99%